2023
DOI: 10.1002/mnfr.202200755
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Targets HSP90β to Alleviate Ulcerative Colitis by Controlling Fatty Acid Synthesis and Subsequent NLRP3 Inflammasome Activation

Abstract: Scope: The purpose of this research is to investigate the specific role of HSP90 paralogs in ulcerative colitis (UC), and to explore the mechanisms behind the inhibitory effects of galangin (Gal) on UC by inhibiting HSP90𝜷 in vivo. Methods and results: In order to achieve this, publicly available gene expression data and molecular biology techniques are used. The results show that the expression of HSP90𝜷 is significantly increased in the mucosal biopsies of UC patients and in the colons of colitis mice, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our study revealed that ethanol stimulated a significantly increased expression of NLRP3, ASC, and caspase-1, as well as that of the proinflammatory cytokines IL-18 and IL-1β. Like other flavonoids, galangin exerts its anti-inflammatory effect by repressing NLRP3 inflammasome activation. , Thus, we wondered whether galangin could protect against ethanol-induced intestinal injury via an NLRP3-related pathway. As expected, galangin relieved the NLRP3 inflammasome activation and its downstream proinflammatory cytokine level enhanced induced by ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that ethanol stimulated a significantly increased expression of NLRP3, ASC, and caspase-1, as well as that of the proinflammatory cytokines IL-18 and IL-1β. Like other flavonoids, galangin exerts its anti-inflammatory effect by repressing NLRP3 inflammasome activation. , Thus, we wondered whether galangin could protect against ethanol-induced intestinal injury via an NLRP3-related pathway. As expected, galangin relieved the NLRP3 inflammasome activation and its downstream proinflammatory cytokine level enhanced induced by ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Through extensive research and clinical application, natural botanical remedies have demonstrated distinct efficacy and reduced toxicity in the treatment of various ailments, gaining gradual acceptance among individuals [ 10 , 11 ]. As one of the most active ingredients in A. officinarum , galangin has shown important effects in the prevention and treatment of many diseases, including but not limited to anti-cancer, regulation of apoptosis and inflammation, cardiovascular diseases, and neurodegenerative diseases [ 12 20 ]. Given the limited research on the therapeutic effects and potential mechanisms of galangin in anti-inflammatory pain, this study aimed to evaluate its anti-inflammatory and analgesic effects and explore its mechanism pathways.…”
Section: Discussionmentioning
confidence: 99%